Developing software for self-absorption correction for gamma spectrometry of soil and water samples based on MCNP5 monte carlo simulations / Eliyeh Zamani ...[et al.] - Zamani, Eliyeh; Sina, Sedigheh; Faghihi, Reza; Rafsanjani, Banafshe Zeinali (Universiti Teknologi MARA Shah Alam, 2020)
Gamma spectroscopy using high purity germanium detectors, HPGe, is one of the most effective methods in determining the concentration of gamma-emitting radionuclides in the environment. The HPGe detector was simulated using MCNP5 Monte Carlo code, whereby the detector calibration curves were obtained at various geometries and heights, and the appropriate software was designed for efficiency calibration. The results obtained in this study show that increasing the height and density of the samples can affect the detector efficiency, as the photon interactions with matter depend on the density and the thickness of the materials. Therefore self-absorption in the samples increases with the thickness and the density of the material. The results indicate there is a strong correlation, i.e., R2>0.98 between the efficiency and the height and the density of the samples. The self-absorption correction was compared using the designed software, and the results of simulations show that the developed software can predict the calibration curves for the new samples in different photon energies with error much less than 1%